Fenomena Madrasah Bubar dan Islamic Fullday School - Fatchurrohman Fatchurrohman (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2007)
The birth of Islamic full-day school (SDIT) brings about the direct or indirect effect to the existence of Islamic elementary schools. several schools in Surakarta and its surroundings are lack of students and some of them break up. based on the observation most of the broken schools were built by the collective societies. conversely, the integrated schools or the full-day schools were usually established and possessed by private owners; thus, the profit oriented management of such schools are more dominant; even though, this assumption is not absolutely always correct.